COVID-19 vulnerability: the potential impact of genetic susceptibility and airborne transmission - Krystal J. Godri Pollitt; Jordan Peccia; Albert I. Ko; Naftali Kaminski; Charles S. Dela Cruz; Daniel W. Nebert; Juergen K.V. Reichardt; David C. Thompson; Vasilis Vasiliou (Human Genomics, 2020)
Abstract The recent coronavirus disease (COVID-19), caused by SARS-CoV-2, is inarguably the most challenging coronavirus outbreak relative to the previous outbreaks involving SARS-CoV and MERS-CoV. With the number of COVID-19 cases now exceeding 2 million worldwide, it is apparent that (i) transmission of SARS-CoV-2 is very high and (ii) there are large variations in disease severity, one component of which may be genetic variability in the response to the virus. Controlling current rates of infection and combating future waves require a better understanding of the routes of exposure to SARS-CoV-2 and the underlying genomic susceptibility to this disease. In this mini-review, we highlight possible genetic determinants of COVID-19 and the contribution of aerosol exposure as a potentially important transmission route of SARS-CoV-2.